2004
DOI: 10.1523/jneurosci.5303-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Pavlovian Fear Conditioning Regulates Thr286Autophosphorylation of Ca2+/Calmodulin-Dependent Protein Kinase II at Lateral Amygdala Synapses

Abstract: Ca2ϩ /calmodulin-dependent protein kinase II (CaMKII) plays a critical role in synaptic plasticity and memory formation in a variety of learning systems and species. The present experiments examined the role of CaMKII in the circuitry underlying pavlovian fear conditioning. First, we reveal by immunocytochemical and tract-tracing methods that ␣CaMKII is postsynaptic to auditory thalamic inputs and colocalized with the NR2B subunit of the NMDA receptor. Furthermore, we show that fear conditioning results in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(118 citation statements)
references
References 59 publications
5
112
0
1
Order By: Relevance
“…CaMKII␣ is found to be distributed throughout the LA and to be postsynaptic to thalamic inputs. In addition, inhibition of CaMKII in the amygdala impairs the acquisition of auditory and contextual fear conditioning (Rodrigues et al, 2004b). BDNF has been shown to induce the phosphorylation of this kinase in neurons (Finkbeiner et al, 1997), and we have previously shown that CaMKII phosphorylation is impaired in trkB PLC/PLC but not trkB SHC/SHC mutant synaptosomal preparations isolated from adult mouse cerebral cortices and stimulated with BDNF .…”
Section: Point Mutation At the Shc Site In Trkb Impairs Specific Amygmentioning
confidence: 82%
“…CaMKII␣ is found to be distributed throughout the LA and to be postsynaptic to thalamic inputs. In addition, inhibition of CaMKII in the amygdala impairs the acquisition of auditory and contextual fear conditioning (Rodrigues et al, 2004b). BDNF has been shown to induce the phosphorylation of this kinase in neurons (Finkbeiner et al, 1997), and we have previously shown that CaMKII phosphorylation is impaired in trkB PLC/PLC but not trkB SHC/SHC mutant synaptosomal preparations isolated from adult mouse cerebral cortices and stimulated with BDNF .…”
Section: Point Mutation At the Shc Site In Trkb Impairs Specific Amygmentioning
confidence: 82%
“…This autophosphorylation is also critical for contextual fear conditioning: training in this task increases autophosphorylation of ␣CaMKII at Thr286 in spines in the lateral amygdala (LA), whereas blockade of activation of CaMKII impairs both synaptic plasticity and fear conditioning in the LA (Rodrigues et al, 2004). Tetanic (Ouyang et al, 1997(Ouyang et al, , 1999Lengyel et al, 2004) or chemically (Makhinson et al, 1999;Lengyel et al, 2004) induced LTP in area CA1 results in longlasting increases in autophosphorylation of ␣CaMKII (Lengyel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although NMDARs that contain the NR2B subunit are prevalent in amygdala neurons (Loftis and Janowsky, 2003;Lopez de Armentia and Sah, 2003;Sah and Lopez De Armentia, 2003;Szinyei et al, 2003;Rodrigues et al, 2004), their role in fear extinction is not known. In addition, previous studies testing the effects of amygdala NMDAR blockade were not able to discriminate between effects on the acquisition or retention of fear extinction (see Introduction), leaving open the question of whether NMDARs in the amygdala are indeed involved in extinction learning.…”
Section: Ifenprodil In the Lateral Amygdala Impairs The Acquisition Omentioning
confidence: 99%